MHealth applications for diabetes: User preference and implications for app development. (December 2016) - Conway, Nicholas; Campbell, Iona; Forbes, Paula; Cunningham, Scott; Wake, Deborah
Increasing diabetes prevalence has led to the need for more sustainable and person-centred services. The diabetes self-care mHealth marketplace is growing, but most effective/valued features are unknown. This study gauges diabetes app user opinion to inform development work. An analysis of diabetes mHealth apps informed design of a questionnaire sent to a random sample of 400 patients stratified by diabetes type and age. Responses were analysed by sub-group, and preferences were compared with current diabetes apps. App features included data storage/graphics, exercise tracking, health/diet, reminders/alarms, education. Questionnaire response rate was 59 per cent (234/400); 144/233 (62%) owned smartphones. Smartphone users expressed preference towards mHealth (101/142 (71%)), although diabetes use was low (12/163 (7%)). Respondents favoured many potential features, with similar preferences between diabetes types. This study demonstrates that while mHealth acceptance is high, current engagement is low. Engagement and functionality could be improved by including stakeholders in future development, driven by clinical/user need.